Religious Commodification in Social Experiments on Zavilda TV's YouTube Channel - Jangki Dausat Fonny; Nurfudiniyah Nurfudiniyah; Lukman Hakim (Medya ve Din Araştırmaları Dergisi, 2024)
Social media, including YouTube, has emerged as a significant aspect of contemporary lifestyles in society. Youtubers need to be able to present interesting content ideas in order to attract more viewers and advertisers. Zavilda TV YouTube Channel turns Islam into a content idea and commodifies it to attract more viewers. Religion and spirituality are no longer something exclusive, but have become a commodity and a public broadcast, used as an object and capital in the political economy of the media. Thus, this study aims to uncover realities that reflect the practice of commodification of religion in the Islamic social experiment targeting women. This research uses a qualitative approach with a literature review. Dialogue manuscripts, titles, video descriptions and thumbnails for Zavilda TV are research objects that are studied using observation and documentation methods. The study of the political economy of media and critical discourse analysis are used to uncover and explain commodification in a more critical and in-depth way. The results found in this study are forms of religious commodification in the form of religious symbols and Islamic songs, as well as religious reflections that are given to the target to make them willing to wear the headscarf. The issue of religious tolerance is also included in the content by targeting women of religions other than Islam to try wearing the headscarf. There is a relationship that is lamely built through the clothing of talent and targets like preachers and mad'u. Zavilda TV attempts to disseminate its understanding of religion. The channel asserts that its interpretation of religious doctrine is accurate and obligatory for all Muslim women, even if some of the remarks given tend to discriminate.